Multi-degree of freedom shake table testing of large-scale structural and geotechnical systems with NHERI-UCSD LHPOST6 - McCartney, John S.; Van Den Einde, Lelli; Morrison, Machel; Palermo, Alessandro; Lotfizadeh, Koorosh; Lai, Chin-Ta; Conte, Joel P. (Frontiers in Built Environment, 2025)
This paper focuses on the abilities of the Large High-Performance Outdoor Shake Table (LHPOST6) at UC San Diego to investigate the combined effects of realistic near-field translational and rotational earthquake ground motions applied as dynamic excitation to 3-D and large- or full-scale structural, geotechnical, or soil-foundation-structural systems. The LHPOST6 supports the advancement of innovative materials, manufacturing methods, detailing, earthquake protective systems, seismic retrofit methods, and construction methods, and is a driving force towards improving seismic design codes and standards and developing transformative seismic-resistant concepts. This paper provides: (i) a brief overview of the 6-DOF capabilities of the LHPOST6 facility; (ii) an overview of the research projects conducted so far at the LHPOST6 facility focusing on the performance of the facility, and (iii) new seismic research opportunities enabled by the LHPOST6 to provide data and fragility information on structural and geotechnical systems that can support the full realization of performance- and resilient-based seismic design.